Study on Heat-induced-shape-shifting-memory Alloy on Motorcycle Body Panel - Muhammad Izzat Nor, Ma'arof; Esmail Rageh, Saad Al-Jaberi; Usman, Shahid; Muhammad Hussain, Ismail; Girma, Tadesse Chala (INTI International University, 2019)
Shape memory alloys (SMAs) have the ability of memorizing the original or pervious states such as size or shape when applied to certain process. The objective of this study was to identify the transformation temperature value for a nickel–titanium (Ni-Ti) sample. The experiment was conducted for a one-way shape memory effects in utilizing the high temperature tube furnace, whilst, the Scanning Electron Microscope (SEM) and Differential Scanning Calorimetry (DSC) were used to examine the sample. The result showed that sample which undergone heat treatment up to 6100C was able to produce the one-way shape effect with better characteristics and better austenite phase recovery rate. From the DSC curve, it was found that the transformation temperature value was within the range of 67 and 680C. The other values obtained via the DSC are as follow: Austenite Start (As) = 760C, Austenite Finish (Af) = 530C, Martensite Start (Ms) = 220C, and Martensite Finish (Mf) = 490C. Based on the result of this study, the two-way shape memory effect experiment could now be performed. For the future, more studies on the nickel–titanium (Ni-Ti) material’s thermomechanical behavior is recommended since the demand in the use of piezoelectric materials and electro-rheological material are rapidly increasing due to their flexible and unique properties.